Board Characteristics of merger and acquisition - Edi, Edi; Lestari, Lydia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study examines the relationship between CEO reputation and buy and hold abnormal return. This research is useful for companies when determining strategies in mergers and acquisitions activities. This research will help companies to further improve the criteria in selecting CEOs and directors. CEOs and directors who are selected according to the criteria, the company will get good corporate governance and will get a lot of strategies, suggestions or opinions from the CEO and directors. The sample of this research is companies that are listed on the Indonesia Stock Exchange. This research is quantitative in nature using secondary data with purposive sampling technique on companies that carry out mergers and acquisitions in 2012 to 2021. The data analysis used is a hypothesis test through the SmartPLS 3 application. This study found that the composition of the board of directors, the size of the board of directors and the dominance of the CEO had no significant effect on buy and hold abnormal return. These results also find that the influence of outside directors and CEO reputation shows a significant effect on the relationship between buy and hold abnormal return.